A Combinatorial Reporter Set to Visualize the Membrane Contact Sites Between Endoplasmic Reticulum and Other Organelles in Plant Cell - Li, Tingting; Xiao, Zhidan; Li, Hongbo; Liu, Chuanliang; Shen, Wenjin; Gao, Caiji (Frontiers in Plant Science, 2020)
The membrane contact sites (MCSs) enable interorganelle communication by associating organelles at distances of tens of nanometers over extended membrane surfaces and serve to maintain cellular homeostasis through efficient exchange of metabolites, lipid and calcium between organelles, organelle fission and movement. Most MCSs and a growing number of tethering proteins especially those involved in mediating the junctions between endoplasmic reticulum (ER) and other organelles have been extensively characterized in mammal and yeast. However, the studies of plant MCSs are still at stages of infancy, at least one reason might be due to the lack of bona fide markers for visualizing these membrane junctions in plant cells. In this study, a series of genetically encoded reporters using split super-folder GFP protein were designed to detect the possible MCSs between ER and three other cellular compartments including chloroplast, mitochondria and plasma membrane (PM) in plant cell. By expressing these genetically encoded reporter in Arabidopsis protoplasts as well as Nicotiana benthamiana leaf, we could intuitively observe the punctate signal surrounding chloroplast upon expression of ER-chloroplast MCS reporter, punctate signal of ER-mitochondria MCS reporter and punctate signal close to the PM upon expression of ER-PM MCS reporter. We also showed that the ER-chloroplast MCSs were dynamic structures that undergo active remodeling with concomitant occurrence of chloroplast dysfunction inside plant cells. This study demonstrates that ER associates with various organelles in close proximity in plant cells and provides tools that might be applicable for visualizing MCSs in plants.